Teleost Fish and Organoids: Alternative Windows Into the Development of Healthy and Diseased Brains - Fasano, Giulia; Compagnucci, Claudia; Dallapiccola, Bruno; Tartaglia, Marco; Lauri, Antonella (Frontiers in Molecular Neuroscience, 2022)
The variety in the display of animals’ cognition, emotions, and behaviors, typical of humans, has its roots within the anterior-most part of the brain: the forebrain, giving rise to the neocortex in mammals. Our understanding of cellular and molecular events instructing the development of this domain and its multiple adaptations within the vertebrate lineage has progressed in the last decade. Expanding and detailing the available knowledge on regionalization, progenitors’ behavior and functional sophistication of the forebrain derivatives is also key to generating informative models to improve our characterization of heterogeneous and mechanistically unexplored cortical malformations. Classical and emerging mammalian models are irreplaceable to accurately elucidate mechanisms of stem cells expansion and impairments of cortex development. Nevertheless, alternative systems, allowing a considerable reduction of the burden associated with animal experimentation, are gaining popularity to dissect basic strategies of neural stem cells biology and morphogenesis in health and disease and to speed up preclinical drug testing. Teleost vertebrates such as zebrafish, showing conserved core programs of forebrain development, together with patients-derived in vitro 2D and 3D models, recapitulating more accurately human neurogenesis, are now accepted within translational workflows spanning from genetic analysis to functional investigation. Here, we review the current knowledge of common and divergent mechanisms shaping the forebrain in vertebrates, and causing cortical malformations in humans. We next address the utility, benefits and limitations of whole-brain/organism-based fish models or neuronal ensembles in vitro for translational research to unravel key genes and pathological mechanisms involved in neurodevelopmental diseases.